Follicle-Stimulating Hormone: A Review of Form and Function in the Treatment of Infertility. (June 2016) - Smitz, Johan; Wolfenson, Claudio; Chappel, Scott; Ruman, Jane
The use of gonadotropin therapy, including follicle-stimulating hormone (FSH), represents an indispensable part of fertility treatment. There are a number of FSH preparations commercially available or in development, including both urinary-derived products (urinary-derived FSH [uFSH]) and FSH produced through recombinant techniques (recombinant FSH [rFSH]). Differences in the glycosylation patterns of FSH give rise to a number of naturally occurring isoforms that may differ functionally. The relative concentrations of these isoforms vary over the course of the menstrual cycle and the lifetime, indicating that these differences in glycosylation may have physiologic relevance. Although both uFSH and rFSH contain human FSH, there are differences in the glycosylation patterns, which may give rise to differences in biologic activity between products. Current FSH products have been shown to have high purity and to exhibit consistent, favorable efficacy and safety profiles for the treatment of infertility, regardless of urinary or recombinant origin.